Leadership of The School Principle in Improving Teacher Performance in Elementary Schools - Hayati, Rahmi; Marzuki, Marzuki; Yus, Anita; Armanto, Dian (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The role of school leadership in improving teacher performance is an important thing to do to produce professional teachers. School principals must have the necessary skills to fulfill their roles effectively and efficiently, maximizing school resourcesThis study employs a purely quantitative methodology. The research subjects include the school principal and three teachers from SD Negeri 5 Juli. Regardless of the method, data collection is carried out through observation, conversation, and documentation. The information is then analyzed by means of data editing, data presentation, and the drawing of conclusions and verification. The purpose of this study is to provide a detailed description of the role of the school principal in boosting teacher performance. Research findings indicate that the role of the head can be improved through teacher competence enhancement (both formally and informally), extensive academic supervision, the development of a productive school culture, and the provision of rewards based on performance. In addition, it's crucial to have resources that aid instructors in their teaching.